Genre Drama sebagai Favorit di Netflix Periode Januari – Juni 2021 - Sitepu, Petrus Damiami; Sudarsono, Kus (Institut Seni Indonesia Yogyakarta, 2023)
Netflix is a film exhibition platform in digital format. Netflix is one of the favourite platforms for film enthusiasts, especially among the respondents in this study. Netflix is included in the Non-Theatrical Exhibition Film category with its popular term Over-The-Top. Netflix is categorized explicitly as SVOD (Subscription Video On Demand). In this study, we do not only look at the categorization of films based on the primary genre but also look at the secondary film genres. According to respondents, the secondary genre of films is one aspect of selecting films on the Netflix platform.This study used a quantitative approach with a cluster random sampling method. The sample used in this research was students of the Film Study Program, Faculty of Art and Design, Multimedia Nusantara University. The results of this study show that in the period January - July 2021, the film Ali & Ratu Ratu Queens is an Indonesian film that many Netflix users watch. In addition, the film Sweet & Sour is the most-watched international film by respondents. Respondents in this study stated that there is a need for film categorization. Still, film categorization is not only based on the primary genre but there needs to be a secondary genre as well. Films in the drama genre are the favourite of the respondents in this study, both primary and secondary drama genres.